Implikasi Yuridis Kontrak Mitra (Disguised Employment) Terhadap Hak Jaminan Sosial Ketenagakerjaan Tenaga Medis dan Tenaga Kesehatan - Mahesa Paranadipa Maykel; Fahmi Hakam (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2025)
Changes in the employment structure in Indonesian healthcare facilities (Fasyankes) over the past decade have shown a significant increase in the use of partner contracts, outsourcing, and independent cooperation agreements for medical and health workers. This employment relationship pattern is considered administratively flexible, but this unclear status is an attempt by Fasyankes to avoid legal obligations (avoidance of liability), particularly the obligation to fulfill the right to protection of Employment Social Security as guaranteed in Law No. 24 of 2011 concerning BPJS, and Law No. 13 of 2003 concerning Manpower as amended by Law No. 06 of 2023 on Job Creation. This article aims to analyze the legal implications of the use of partner contracts on the fulfillment of BPJS Employment membership rights for healthcare workers, identify regulatory and implementation gaps, and formulate policy recommendations to ensure the fulfillment of social protection rights in accordance with national legal standards and global health employment practices. The research method used a literature review approach, with a Statute Approach and a Conceptual Approach (the principle of Substance over Form), utilizing analysis of laws and regulations, policy documents, and case studies of employment law in the health sector in Indonesia. The analysis shows that